2007
DOI: 10.1080/17453670710013717
|View full text |Cite
|
Sign up to set email alerts
|

Tartrate-resistant acid phosphatase 5b (TRAP 5b) as a marker of osteoclast activity in the early phase after cementless total hip replacement

Abstract: Background After total hip replacement, increased bone metabolism is seen. A local periprosthetic osteopenia can be measured by dual-energy X-ray absorptiometry (DXA), but it is still unkown whether biochemical markers can be used to monitor the local remodeling at an earlier stage.Patients and methods In this prospective study we compared the biochemical markers tartrate-resistant acid phosphatase 5b (TRAP 5b), bone ALP, osteocalcin and CrossLaps with periprosthetic DXA in 17 consecutive patients after unceme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 14 publications
(17 reference statements)
4
20
1
Order By: Relevance
“…Here we show that TRACP and cathepsin K expression are upregulated in prelamin A-accumulating cells. Although these factors are known to mediate bone resorption [Avnet et al, 2006;Habermann et al, 2007], osteoclasts obtained in our experimental model failed to show efficient resorptive activity. This finding implies that prelamin A triggers other pathways or alters the timing of gene expression thus leading to formation of osteoclasts with reduced resorption activity.…”
Section: Discussioncontrasting
confidence: 56%
“…Here we show that TRACP and cathepsin K expression are upregulated in prelamin A-accumulating cells. Although these factors are known to mediate bone resorption [Avnet et al, 2006;Habermann et al, 2007], osteoclasts obtained in our experimental model failed to show efficient resorptive activity. This finding implies that prelamin A triggers other pathways or alters the timing of gene expression thus leading to formation of osteoclasts with reduced resorption activity.…”
Section: Discussioncontrasting
confidence: 56%
“…TRAP is synthesized by different cells from the monohistiocytic lineage. It is also found in placenta, macrophages and leukocytes, but it is most significant expression occurs in osteoclasts, what renders this enzyme a marker of bone resorption (Miyazaki et al 2003;Fukushima et al 1991;Habermann et al 2007). In the interior of the cells, TRAP is found mainly in lysosomes, and, secondarily, in the cytoplasm or in the extracellular matrix.…”
Section: Introductionmentioning
confidence: 97%
“…These markers include osteocalcin, an osteoblast-specific bone formation marker, and TRAP, an osteoclast-specific bone resorption marker (Habermann et al, 2007;Tang et al, 2011). Our study found that RYR extract decreased the bone turnover rate by suppressing osteoclast activity in OVX rats.…”
Section: Discussionmentioning
confidence: 52%